Standardization Analysis of Vasectomy Acceptance in the Family Māqāṣid āl-Syārī'āh Perspective - Lidia Sandy Kartika; Mufidah Ch; Abd. Rouf (Studi Multidisipliner: Jurnal Kajian Keislaman, 2026)
This study examines the acceptance of vasectomy procedures in the family from the perspective of Maqasid al-Sharia, emphasizing the application of sharia objectives in determining the legal and ethical limits of vasectomy implementation. This research focuses on how the principles of the protection of the soul (hifz al-nafs), heredity (hifz al-nasl), reason (hifz al-'aql), religion (hifz al-din), and property (hifz al-mal) can be used as a basis for consideration in the standardization of vasectomy procedures. This research uses a normative qualitative approach through literature studies by analyzing scientific journals, classical and contemporary fiqh literature, and fatwa of the Indonesian Ulema Council. The data were analyzed descriptively and interpretively to identify the relevance between medical procedures and the principles of Islamic law. The results of the study show that vasectomy can be accepted on a limited and conditional basis in Islam if it is done based on medical needs, consent of both partners, in accordance with medical standards, and considering the benefits that outweigh the potential harms. In addition, the procedure must not contradict the basic principles of sharia and must remain within the framework of maintaining family welfare and social harmony. The study concludes that the standardization of vasectomy procedures is essential to ensure medical safety, ethical responsibility, and conformity with the objectives of Maqasid al-Sharia. Therefore, systematic and structured guidelines are needed so that the practice of vasectomy can be carried out safely, ethically, and in accordance with sharia principles in the life of modern society.